Advancements in Diagnostic Technology: The Role of Automation in Modern Medical Laboratories - Nabil Saad Muftah Mohammed (African Journal of Advanced Pure and Applied Sciences, 2024)
The integration of automation in medical laboratories has revolutionized diagnostic practices, enhancing accuracy, efficiency, and patient care. This paper explores how technologies such as Artificial Intelligence (AI), Robotic Process Automation (RPA), the Internet of Medical Things (IoMT), and nanotechnology are transforming traditional workflows, enabling faster and more precise diagnostics. Case studies from leading healthcare institutions, including Mayo Clinic, Cleveland Clinic, and Johns Hopkins Hospital, demonstrate significant improvements in diagnostic outcomes, reduced processing times, and increased detection rates. However, challenges such as high costs, technical integration, workforce training, and ethical concerns persist, limiting widespread adoption. The study synthesizes these benefits and challenges, linking automation’s potential with healthcare’s overarching goals of accuracy, efficiency, and patient-centered care. It concludes that while barriers remain, a strategic approach involving investment, policy development, and workforce education is essential for maximizing automation’s impact in diagnostics.